PtiCYP85A3, a BR C-6 Oxidase Gene, Plays a Critical Role in Brassinosteroid-Mediated Tension Wood Formation in Poplar - Jin, Yanli; Yu, Chunyan; Jiang, Chunmei; Guo, Xiaotong; Li, Bei; Wang, Cuiting; Kong, Fanjing; Zhang, Hongxia; Wang, Haihai (Frontiers in Plant Science, 2020)
In angiosperm trees, the gelatinous layer (G-layer) takes a great part of the fiber cell wall in the tension wood (TW). However, the mechanism underlying G-layer formation in poplar is largely unknown. In this work, we demonstrate that G-layer formation in poplar TW cells is regulated by brassinosteroid (BR) and its signaling. PtiCYP85A3, a key BR biosynthesis gene, was predominantly expressed in the xylem of tension wood, accompanied with a relatively higher castasterone (CS) accumulation, than in the xylem of opposite wood (OW). A wider expression zone of BZR1, a key transcriptional factor in BR singling pathway, was also observed in G-fiber cells on TW side than in wood fiber cells on the OW side, as indicated by immunohistochemistry assays. Transgenic poplar plants overexpressing PtCYP85A3 produced thicker G-layer with higher cellulose proportion, and accumulated more BZR1 protein in the xylem of TW than did the wild type (WT) plants. Expression of most tension wood-associated CesAs, which were induced by 2, 4-epibrassinolide, an active BR, and inhibited by brassinazole, a BR biosynthesis inhibitor, were also up-regulated in the xylem of tension wood in transgenic plants compared to that in WT plants. Further studies with dual-luciferase assays demonstrated that the promoters of PtiCesAs were activated by PtiMYB128, a tension wood specific transcription factor, which was then regulated by BZR1. All these results indicate that BR plays a crucial role in the G-layer formation of tension wood fiber cells by regulating the expression of BZR1, PtiMYB128 and PtiCesAs in poplar.